Communicating about Zoonotic Parasites in Pursuit of Public Health: Transmission and Prevention at the Human-Wildlife Interface - Buller, Elizabeth (My University, 2025)
North America is home to a multitude of zoonotic parasites and their wildlife hosts. The evolving human-wildlife interface presents many opportunities for zoonotic spillover, especially through wildlife-centric activities such as hunting, trapping, research, or conservation. This Applied Practice Experience (APE) seeks to characterize the risk posed by zoonotic parasites in wildlife, identify species of concern, recognize points of zoonotic transmission, and formulate preventive strategies. This information is organized and condensed into two products: an evidence-based, best-practice manual covering select zoonotic endoparasites in North American wildlife, and a commentary article discussing the key points regarding zoonotic parasitic transmission and prevention. Both products are tailored to a largely non-academic audience, implementing multimodal communication strategies to translate key concepts from scientific literature to accessible materials while preserving scientific integrity. This portfolio required a multidisciplinary approach inclusive of the public health, veterinary, and wildlife fields and emphasizes the importance of systems thinking when addressing the complexities of zoonotic disease transmission.
Keywords: zoonotic parasitology; emerging infectious disease; human-wildlife interface; one health